Pengaruh Gaya Kepemimpinan dan Fasilitas Kerja terhadap Kinerja Aparatur Sipil Negara di Lingkungan Kecamatan Batam Kota - R. Putri Anggita Permatasari; Timbul Dompak (Universitas Batanghari Jambi, 2023)
Leadership style and work facilities are important factors in improving the performance of civil servants. Leadership style is the behavior or method used by a leader in influencing the thoughts, feelings, attitudes and behavior of members or subordinates. While work facilities are supporting facilities in the company's activities in physical form, and are used in normal company activities, have a relatively permanent period of use and provide benefits for the future. This study aims to analyze the effect of leadership style (X1) and work facilities (X2) on the performance of civil servants (Y) in the Batam City District. The approach in this research uses quantitative methods, distribution through questionnaires between respondents. The sample of this research is 101 people. The results of this study indicate that; (1) there is an influence of leadership style on the performance of civil servants with a total value of t count (3,063) > t table (1,984), (2) partially there is an effect of work facilities on the performance of asn with a value of t count (11,490) > t table (1,984) , (3) at the same time there is an influence of leadership style and work facilities on the performance of civil servants with the number F (259.544) > F table (3.09).